2015
DOI: 10.7897/2277-4343.06497
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Modulation of Thyroid Function in Forced Cold Water Swimming Stress Induced Wistar Albino Rats

Abstract: The present study was undertaken to provide experimental evidence for vestibular modulation of thyroid function in cold water swimming stress induced wistar albino rats and to suggest further research to recommend vestibular stimulation as an intervention for thyroid disorders. 24 healthy, adult male albino rats of wistar strain were used in the present study. Rats were forced to swim in the plastic tubs (height: 60 cm, diameter: 40 cm) containing cold water, maintained at 10°C. Depth of the water in the plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that stress can induce negative effects on thyroid secretion, much like cortisol, through interactions with the hypothalamic–pituitary–adrenal axis, so it is interesting that vestibular stimulation not only negated the expected actions on thyroid function, but also reduced the subjective feeling of stress as reported by study participants. Indeed, vestibular stimulation in rats subjected to a stressor environment induced by cold water swimming is reported to prevent stress‐mediated changes in thyroid function, cholesterol and body weight over a period of 15 days . Taken together, it appears that the mechanism by which vestibular stimulation influences the thyroid therefore is twofold, comprising both direct and indirect actions.…”
Section: Vestibular Influences Of the Neuroendocrine Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that stress can induce negative effects on thyroid secretion, much like cortisol, through interactions with the hypothalamic–pituitary–adrenal axis, so it is interesting that vestibular stimulation not only negated the expected actions on thyroid function, but also reduced the subjective feeling of stress as reported by study participants. Indeed, vestibular stimulation in rats subjected to a stressor environment induced by cold water swimming is reported to prevent stress‐mediated changes in thyroid function, cholesterol and body weight over a period of 15 days . Taken together, it appears that the mechanism by which vestibular stimulation influences the thyroid therefore is twofold, comprising both direct and indirect actions.…”
Section: Vestibular Influences Of the Neuroendocrine Systemmentioning
confidence: 99%
“…Given the apparent links with the arcuate nucleus and the paraventricular nucleus of the hypothalamus, vestibular stimulation has been suggested as a supplementary therapy for thyroid disorders . Indeed, vestibular stimulation is reported to positively influence thyroid hormone secretion in both animals and humans in response to environmental stress . For example, it was shown that daily vestibular stimulation for a period of 2 months in female participants with premenstrual syndrome, not only decreased and increased secretion of thyroid‐stimulating hormone and thyroxine, respectively, but also reduced perceived stress .…”
Section: Vestibular Influences Of the Neuroendocrine Systemmentioning
confidence: 99%
“…This is proof to explain that not just basal ganglia are involved in the somato-motor loop, but it also requires occulomotor loop related to frontal sub cortical circuit (Joti et al, 2007). PD patients do complain dysfunction of the cardiac autonomic system as they reported reduced blood pressure and the reduced response of heart rate on autonomic stimulation (Varghese et al, 2015). Many Ayurvedic thera- pies like massages using medicinal oils, natural gait correcting exercises, etc; are in practice to treat and manage the PD disease (Kishore et al, 2010).…”
Section: Resultsmentioning
confidence: 79%
“…The newest popular therapy is the application vestibular stimulation for developmentally delayed children. The extensive preliminary studies demonstrated that the application of controlled vestibular stimulation through swing serves as an intervention for learning disability and also learnt that it would relieve stress, promotes sleep further improves immunity, relieves cancer pain, and also to treat the endocrine disorders (Varghese et al, 2015). The study conducted in Wistar albino rats by application of cold water vestibular stimulation had shown the suppression of the stress-induced changes observed under immunological parameters (Purushothaman et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…First three years of medical education was reported to be more stressful and higher stress was reported in females 14 . Significantly higher depression and stress levels were reported in female students 15 . Animal and human studies reported that increase in the body weight was observed followed by stress 16,17 .…”
Section: Discussionmentioning
confidence: 81%